Effect of Different Roofing Material on Body Weight and Feed Intake of Indigenous Sheep under Stall Feeding System - Khant, Malhar; Patel, Nitin R.; Modi, Rakesh J.; Wadhwani, Kishan N. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study was conducted to assess the effect of roof on body weight and feed intake of sheared and non-sheared sheep under stall feeding system in the hot dry season. Adult dry indigenous sheep (24) were distributed randomly into two treatment groups, i.e., T1: asbestos roof and T2: agro - net roof. Each treatment comprised of six sheared and six non-sheared animals. Sheep were provided with total mixed ration in morning, afternoon and night individually. The bodyweight of sheared (31.87 ± 2.14, 31.96 ± 1.55 kg) and non-sheared (32.16 ± 1.59, 32.42 ± 1.42 kg) animals was comparable between roof treatments. The experimental animals reared under agro-net roofed shelter consumed significantly (p <0.05) more dry matter and nutrients as compared to animals reared under asbestos roofed shelter. Dry matter and nutrient intake of sheared sheep were significantly (p <0.05) higher as compared to non-sheared sheep under agronet and asbestos roofed shelter. The results indicated that the sheep can be reared comfortably under agronet roof without affecting feed and nutrient intake.